65.9k views
2 votes
Ln(x+1)3=3

ln
(
x
+
1
)
=
3
Question 7 options:

Ln(x+1)3=3 ln ( x + 1 ) = 3 Question 7 options:-example-1

2 Answers

5 votes

Explanation:


In(x + 3)^(3) = 3 \\ \therefore \: 3In(x + 3) = 3 \:\\ \therefore \: In(x + 3) = (3)/(3) \: \\ \therefore \: In(x + 3) = 1\\ \therefore \: In(x + 3) = In \: 10\\..( \because \: In \: 10 = 1) \\ \therefore \:x + 3 = 10 \\ \therefore \:x = 10 - 3 \\ \: \: \: \: \: \huge \red{ \boxed{\therefore \:x = 7}}

User Andreabedini
by
5.0k points
7 votes

Answer:

x=e-1 0r 1.71828

Explanation:

User Patzm
by
5.5k points